1981
DOI: 10.1002/aja.1001600104
|View full text |Cite
|
Sign up to set email alerts
|

Degenerative changes in endothelial and smooth muscle cells from aging swine ductus arteriosus and venosus

Abstract: Degenerative changes in endothelial and smooth muscle cells from fetal, 2-month-, and 6-month-old swine ductus vasculature were observed. In fetal ductus, a discontinuous internal elastic lamina and increased extracellular mucopolysaccharide deposition were initially noted. At 2 months of age, there was widespread fibromuscular intimal thickening, the appearance of modified smooth muscle cells, increased medial fibrosis, and the occurrence of cell debris and nuclear pyknosis. Early modification of smooth muscl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

1983
1983
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 13 publications
2
3
0
Order By: Relevance
“…An increase in number of these bodies following modifications in the functional and structural characteristics of the endothelial wall has never been described in lymphatic vessels but has been described in blood vessels. Their increase had been connected to the fibrotic processes which the blood vessels were undergoing (Toda et al, 1981;Kagawa and Fujimoto, 1987). This hypothesis could also support our observations on the increase of the Weibel-Palade bodies in the lymphatic vessels of fibrotic pulps.…”
Section: Discussionsupporting
confidence: 89%
“…An increase in number of these bodies following modifications in the functional and structural characteristics of the endothelial wall has never been described in lymphatic vessels but has been described in blood vessels. Their increase had been connected to the fibrotic processes which the blood vessels were undergoing (Toda et al, 1981;Kagawa and Fujimoto, 1987). This hypothesis could also support our observations on the increase of the Weibel-Palade bodies in the lymphatic vessels of fibrotic pulps.…”
Section: Discussionsupporting
confidence: 89%
“…These types of cell degeneration differed from total cell death and focal cytoplasmic necrosis. (Toda et al 1981(Toda et al , 1983) These aneurismic lesions were similar to those found in Marfan's syndrome in human and also in copper deficiencies and f3-aminopropionitrile treatments in animals (Simpson et al 1980 ).…”
Section: Resultssupporting
confidence: 57%
“…The DV has been described in fetuses of mice27, 28, rats29, dogs30–33, cats34, 35 and many other mammals. However, guinea pig and horse fetuses do not have a DV at term36–38. In pig fetuses, the DV disappears during intrauterine life39, 40, while in sheep fetuses the DV increases in size up to birth as a short‐circuit for re‐oxygenated blood returning from the placenta36.…”
Section: Anatomical Structure and Histology Of The Ductus Venosus In mentioning
confidence: 99%